2012
DOI: 10.1093/jrr/rrs057
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the inhibitory effects of antioxidant vitamins and radon on carbon tetrachloride-induced hepatopathy

Abstract: We have previously reported that radon inhalation activates anti-oxidative functions and inhibits carbon tetrachloride (CCl4)-induced hepatopathy. It has also been reported that antioxidant vitamins can inhibit CCl4-induced hepatopathy. In the current study, we examined the comparative efficacy of treatment with radon, ascorbic acid and α-tocopherol on CCl4-induced hepatopathy. Mice were subjected to intraperitoneal injection of CCl4 after inhaling approximately 1000 or 2000 Bq/m3 radon for 24 h, or immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…They reported that vitamin C normalized levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, blood hydrogen peroxide and malondialdehyde in liver of carbon tetrachloride intoxicated rats. The ability of vitamin C to prevent Carbon tetrachloride induced hepatotoxicity in rats was also reported by some authors (Ademuyiwa et al, 1994;Kataoka et al, 2012).…”
Section: Introductionsupporting
confidence: 62%
“…They reported that vitamin C normalized levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, blood hydrogen peroxide and malondialdehyde in liver of carbon tetrachloride intoxicated rats. The ability of vitamin C to prevent Carbon tetrachloride induced hepatotoxicity in rats was also reported by some authors (Ademuyiwa et al, 1994;Kataoka et al, 2012).…”
Section: Introductionsupporting
confidence: 62%
“…However, these substances are not easily available. Vitamin C has anti-oxidative activities and is contained in numerous vegetables and fruits (31)(32)(33). The present study therefore assessed whether vitamin C can suppress AA-induced cytotoxicity to kidney cells.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetyl cysteine (NAC) and glutathione (GSH), anti-oxidative agents, were studied to prevent cell death through AA treatment (16). Vitamin C is a common nutrient with anti-oxidative properties (31)(32)(33). In the present study, it was hypothesized that vitamin C is able to inhibit AA-induced cytotoxicity.…”
Section: Vitamin C Attenuates the Toxic Effect Of Aristolochic Acid Omentioning
confidence: 98%
“…These groups were exposed to 0, 3.125, 6.25, and 12.5 mg/kg/day SWCNTs, 23 6.25 mg/ kg/day SWCNTs + 100 mg/kg/day ascorbic acid (block group), and 100 mg/kg/day ascorbic acid. 24 We intravenously injected the suspension daily through the tail vein. 18 Based on the period of ethological analysis we adopted in this study, International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 15-Jul-2020 For personal use only.…”
Section: Experimental Protocolmentioning
confidence: 99%